AN EFFICIENT STATIONERY VENDING MACHINE USING RFID CARD - R, Preetilatha; R, Ramkumar; M, Bharani (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
Since their introduction, vending machines became associate degree more and more vital marketing publically and personal sectors .In instructional establishments and offices stationery vending machine is of nice importance. this technique proposes a microcontroller based vending machine that dispatches A4 sheets, pencil ,pen , etc., once the RFID card is scan. The users will choose the desired item once the card is scanned and collect the item within the output unit. The system is split into 3 components, the primary half deals with the scanning of RFID card that provides cashless payment. The second is that the programming unit that is enforced using FreeRTOS. The third half is that the show unit that displays info and delivers the desired item supported the knowledge sent from the microcontroller. an embedded system based vending machine is intended to attain an occasional value , accurate, and transportable machine which will sale the letter paper things mechanically